Transformation of amorphous carbon to graphene on low-index Ni surfaces during rapid thermal processing: a reactive molecular dynamics study - Li, Xiaowei; Wang, Aiying; Lee, Kwang-Ryeol (ROYAL SOC CHEMISTRY, 2019)
The transformation of amorphous carbon to graphene on different Ni surfaces during rapid thermal processing was explored using reactive molecular dynamics simulation. Due to the difference in activation energy, Ni surfaces affected the diffusion behavior of C into Ni and thus modulated the remnant number of C atoms, dominating the formation and quality of graphene, which accorded with the developed empirical equation.
Keywords: GROWTH; FILMS; METHANE